Guardians of the Cell: Effector-Triggered Immunity Steers Mammalian Immune Defense. Issue 10 (October 2019) - Kufer, Thomas A.; Creagh, Emma M.; Bryant, Clare E.
Abstract : The mammalian innate immune system deals with invading pathogens and stress by activating pattern-recognition receptors (PRRs) in the host. Initially proposed to be triggered by the discrimination of defined molecular signatures from pathogens rather than from self, it is now clear that PRRs can also be activated by endogenous ligands, bacterial metabolites and, following pathogen-induced alterations of cellular processes, changes in the F-actin cytoskeleton. These processes are collectively referred to as effector-triggered immunity (ETI). Here, we summarize the molecular and conceptual advances in our understanding of cell autonomous innate immune responses against bacterial pathogens, and discuss how classical activation of PRRs and ETI interplay to drive inflammatory responses. Highlights: Pathogen-mediated alterations in the cellular environment can contribute to mammalian innate immunity in a process referred to as effector triggered immunity (ETI). Host-derived second messengers and metabolites are emerging as triggers of innate immune pathways. Subcellular receptor localization, the cytoskeleton, and other cellular components can play key roles in mammalian ETI. Coactivation of PRRs and ETI may be required for maximal activation of innate immunity.